Whence Come Qurʾān Manuscripts?: Determining the Regional Provenance of Early Qurʾānic Codices - Vahidnia, Ala (Der Islam, 2021)
In studies of early Qurʾānic manuscripts, determining the provenance of these manuscripts is a thorny issue because in most cases they lack endowment notes or colophons. The reports in early Islamic sources regarding textual variants of regional codices ( maṣāḥif al-amṣār ) may contribute to find a solution to this problem. A list of regional variants, mostly based on al-Dānī’s al-Muqniʾ, can be found in Nöldeke et al.'s The History of the Quran. However, as the authors have stated, a comparison of some of the early Qurʾānic manuscripts in the Topkapı Sarayı Museum with this table of maṣāḥif al-amṣār variants indicates that the traditional reports are unreliable for identifying the provenance of Qurʾānic manuscripts because none of these codices can be attributed to any particular region. The present article is an attempt to demonstrate that this problem results from relying solely on the data provided by al-Dānī and ignoring earlier and more significant sources, such as al-Sijistānī’s Kitāb al-Maṣāḥif. It attempts to provide a new and more precise classification of regional variants by reading afresh the reports on the features of maṣāḥif al-amṣār , taking into account the sources which were not used by Nöldeke et al., especially al-Sijistānī’s Kitāb al-Maṣāḥif, thus making the list of maṣāḥif al-amṣār variants more accurate, thereby the variants of each of these early Qurʾānic Codices tally more with the reports preserved for the characteristics of one of the maṣāḥif al-amṣār in literary sources. As the texts of the surviving manuscripts are not of a diverse nature we are able, with some certainty, to draw conclusions that substantiate the reports as to the peculiarities of the muṣḥaf s of different cities.